2006
DOI: 10.1007/s10495-006-9787-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intracellular ascorbate on the susceptibility of HL60 and Jurkat cells to chemotherapy agents

Abstract: Chemotherapy agents initiate tumour cell apoptosis and this is thought to involve oxidative stress. In this study we have investigated the effect of the important antioxidant Vitamin C (ascorbate) on the response of HL60 and Jurkat cells to three chemotherapy drugs, namely etoposide, melphalan and arsenic trioxide (As(2)O(3)). Cells grown in routine culture media are deficient in ascorbate and to determine its effect on chemotherapy drug-induced apoptosis we supplemented the cells prior to drug exposure. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 57 publications
3
4
0
Order By: Relevance
“…This difference may result in the fundamental difference in the metabolism of Me 2 S 4 , which was involved in radical reactions with the myeloperoxidase, an enzyme that is abundant in HL-60 cells. 26) Taken together, our observations indicate that Me 2 S 3 and Me 2 S 4 induced the generation of reactive oxygen species, and that subsequent caspase-3 activation initiated apoptosis in Jurkat and HL-60 cells. Factors other than the GSH content may have been involved in determining the cell damage such as an alteration in the membrane phospholipids.…”
Section: Discussionsupporting
confidence: 62%
“…This difference may result in the fundamental difference in the metabolism of Me 2 S 4 , which was involved in radical reactions with the myeloperoxidase, an enzyme that is abundant in HL-60 cells. 26) Taken together, our observations indicate that Me 2 S 3 and Me 2 S 4 induced the generation of reactive oxygen species, and that subsequent caspase-3 activation initiated apoptosis in Jurkat and HL-60 cells. Factors other than the GSH content may have been involved in determining the cell damage such as an alteration in the membrane phospholipids.…”
Section: Discussionsupporting
confidence: 62%
“…High-dose ascorbic acid inhibits HL-60 cell growth, whereas a low-dose does not. Previous studies have demonstrated that a high-dose of ascorbic acid can increase radiation-induced and etoposide-induced apoptosis in HL-60 cells (28,29). Similar to these studies, the present study demonstrated that a high-dose (5 µM) of ascorbic acid inhibited cell growth in the HL-60 cells, whereas a low-dose (5 µM) had no affect on the growth of the HL-60 cells (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Previous studies have demonstrated that ascorbic acid can activate the ERK signaling pathway to induce progenitor cell differentiation (26,27). Additionally, several studies have demonstrated that high-doses of ascorbic acid (>100 µM) can activate a caspase cascade to promote radiation-induced and etoposide-induced apoptosis in HL-60 cells (28,29). A previous study also demonstrated that high-doses of ascorbic can induce HL-60 cell apoptosis and induce a fraction of HL-60 cells to express the granulocyte marker, CD 66b (30).…”
Section: Ascorbic Acid Inhibits Tpa-induced Hl-60 Cell Differentiatiomentioning
confidence: 99%
“…10) This difference may originate from a fundamental difference in the metabolism of -carotene assisted by UVA irradiation, which involves radical reactions with myeloperoxidase, an enzyme that is abundant in HL-60 cells. 19) Without UVA irradiation, co-treatment withcarotene significantly enhanced the caspase-3 activity (Fig. 6B), even though it had no significant effect on the cell viability and intracellular ROS level induced by Me 2 S 4 (Figs.…”
Section: Discussionmentioning
confidence: 93%